Can Risk Tolerance Moderate Financial Literacy and Internet Banking Behavior During Covid-19? - Fida Muthia; Nyimas Dewi Murnila Saputri; Sri Andaiyani; Agil Novriansa (University of Merdeka Malang, 2022)
This study aims to examine whether risk tolerance can moderate the relationship between financial literacy on Internet banking behavior during Covid-19. 133 respondents are chosen as the sample of this study through purposive sampling with criteria. The hypothesis testing of this research was carried out using two models, namely, the direct relationship model and the moderation model. The results show that financial literacy has a positive effect on Internet banking. However, risk tolerance is unable to be a moderating variable. The results give the implication that Internet banking users can be increased by improving financial literacy, and financial risk may not be a significant driver in the use of internet banking during Covid-19.